Keputusan Berkunjung Ditinjau D ari Media Promosi, Daya Tarik, dan Citra Destinasi Pada Wisata Tegal Simbah Girimarto Wonogiri - Hanny Safitri, Dea Livoine; Mursito, Bambang; Diyah, Ida Aryati (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of Promotion Media, Attraction, and Destination Image on the Decision to Visit Tegal Simbah Girimarto Wonogiri Tourism. This tpe of research uses a quantitative descriptive approach. The population in this study was 5900 visitors to Tegal Simbah Girimarto Wonogiri Tourism. While the sample in this study amounted 360 respondendts using the sampling techique, namely the incidental sampling techjique because anyone who accidentally meets the researcher can be used as a sample. Data collection in this study used a questionnaire with a Likert scale to measure respondents’ answers. The results of this study indicate that promotional media, attractions, and destination image have a significant and positive effect on the decision to visit Tegal Simbah Girimarto Wonogiri Tourism. This can be proven by the results of the Determination Coefficient (R2) which is 42,8%, while the reamining 57,2% is influenced by other things or other variables not examined in this study.Keyword: Promotional Media, Attraction, Destination Image, Visiting Decision.